Prospective implementation of a standardized screening protocol for deep venous thrombosis in abdominal surgical oncology patients. Issue 3 (16th August 2018) - Sinnamon, Andrew J.; Tong, Jason K. C.; Bailey, Elizabeth A.; Brown, Caitlin; Colbert, Latesha; Murray, Shannon; Jackson, Benjamin M.; Roses, Robert E.
Abstract : Background and Objectives: Venous thromboembolism (VTE) remains a major cause of perioperative morbidity and mortality despite implementation of prophylaxis guidelines. We sought to identify risk factors for occult deep venous thrombosis (DVT) following abdominal surgery for cancer and measure the clinical impact of a prospectively implemented standardized postoperative DVT screening protocol. Methods: Patients undergoing abdominal surgery for malignant indication were screened with early postoperative lower extremity duplex to identify DVT. Clinical and pathologic factors associated with DVT were identified. Results: Among 255 patients meeting study criteria, 25 (9.8%) had occult lower extremity DVT on routine postoperative screening. Prior history of VTE and lower preoperative hemoglobin were independently associated with DVT (OR, 9.05; P = 0.004; and OR, 1.27; P = 0.025, respectively). Preoperative chemotherapy within 1 year and thrombocytopenia were associated with DVT in univariate analyses only. Five patients developed postoperative pulmonary emboli (2.0%); three following negative duplex and two following positive duplex for distal DVT for which the patients were not therapeutically anticoagulated due to a contraindication. There were no pulmonary emboli in duplex‐positive patients who were anticoagulated or who had vena cava filter placed. Conclusion: Despite prophylaxis, the prevalence of occult DVT in abdominal oncologic surgery patients is considerable. Postoperative screening duplex can identify these events to guide management.